Agricultural production at the oblast level in post-Soviet Kyrgyzstan, 1990-2014: Implications of demographic and climate changes - Guangqing Chi; Jing Gao; Donghui Wang; Annelise Hagedorn; Kamilya Kelgenbaeva; M. Luke Smith; Geoffrey M. Henebry (Research in Globalization, 2020)
Increasing agricultural production is essential for reducing food insecurity, which continues to be a major challenge faced by many developing countries. Here, we examine agricultural production-both crop and livestock-in association with demographic and climate changes from 1990 through 2014 in Kyrgyzstan, an understudied, disadvantaged, mountainous Central Asian country that experienced dramatic changes in political and market structures, rapid demographic changes, and climatic changes during the study period. Results indicate that crop and livestock productions, which are correlated with food security, experienced dramatic changes in the study period. The total fertility rate was found to have a negative association with livestock production. Precipitation and temperature measures had statistically significant and strong correlations with both crop and livestock productions, but their significance diminished dramatically when considered together with socioeconomic factors, regional variation, and temporal change. There were strong correlations among demographic, climatic, and socioeconomic factors, making it challenging to separate their individual attributions to the changes of agricultural production. Overall, a wetter and colder climate was associated with agricultural production increases. However, the growing season from 1991 through 2014 in Kyrgyzstan has become drier and hotter, challenging future agricultural production. This study provides insights into agricultural production and food security in relation to demographic and climate changes in Central Asia.
Keywords: 330; Climate change; Crop production; Food security; High-elevation communities; Kyrgyz Republic; Livestock production; Sociodemographic change